Influence of sociocultural factors on the risk of eating disorders among King Abdulaziz University students in Jeddah, Saudi Arabia - Lina O Aldakhil; Bahaa A Abaalkhail; Ibrahim I Abu (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: In Saudi Arabia, there is not much research on the risk of eating disorders and the influence of sociocultural factors on increasing the risk among university students. The objective of this study was to assess the prevalence of the risk of eating disorder (EDs) in King Abdulaziz University students, the influence of sociocultural factors, and any differences between males and females. MATERIALS AND METHODS: A cross-sectional study was conducted on 763 university students in Jeddah, Saudi Arabia. The data were collected in 3 months from February 2021 to April 2021. A self-administered Eating Attitude Test-26 scale was used to assess the risk of eating disorder among the students. The sociocultural attitude toward appearance questionnaire was used to measure the internalization of thinness, masculinity, and family, peer, and media attitude toward appearance. To test for statistical significance, t-test was used for continuous variables, whereas Ch-square test was performed for categorical variables. Logistic regression analysis were performed to determine factors associated with ED risk; all tests were performed at 0.05 significance level. RESULTS: The prevalence of the risk of eating disorder among the students was observed as 34%. The sociocultural attitude toward appearance was significantly higher among at risk of eating disorder students. The multiple logistic regression analysis showed that females are twice more likely to be at risk for eating disorder than males (2.25) with 95% confidence interval (1.50,3.39). Peer influence was significantly higher among males than females; however, females were significantly more influenced by the media than males. CONCLUSION: The prevalence of eating disorder risk in Saudi university students in Jeddah was observed as alarming and highly influenced by sociocultural factors; therefore, screening university students for eating disorder is very necessary. In addition, there should be media and health promotion campaigns on eating disorder and body image issues.